SENSITIVITAS OPSI PENGEMBANGAN UNIT PENANGKAPAN IKAN TERPILIH DI KABUPATEN LAMPUNG SELATAN - Meizar Malanesia; John Haluan; Hartrisari Hardjomidjojo; Domu Simbolon (Buletin PSP, 2008)
This study is conducted on the waters of South Lampung Regency. It requires data and information on the potential natural resources, human resources, institutions, and facilities and infrastructure. The data and information on catchment fishery will become a priority for analysis. An analysis is also made to determine a standard for fish catching units covering biological, environmental, sustainable, and financial feasibility aspects. The next step is to conduct an integrated analysis of all aspects in relation to the development of seven fish catching units selected, to make priorities of development, and to determine the sensitivity of the development against any possible changes. It is expected that the analysis of fish resources and selection of fish catching units can solve the problems of catchment fishery in the region, and help fishermen to increase productivity. The increased fish production will give a significant contribution to the development of fish businesses and fishermen’s income. With an increased income, it is certainly expected that the fishermen’s welfare will also improve.